Western Colonialism in the Muslim World: A Historical Analysis of the Forms and Mechanisms of Domination: Kolonialisme Barat terhadap Dunia Islam: Analisis Historis atas Bentuk dan Mekanisme Dominasi - Abdalah, Mohammad Ulil Albab (Direktorat Pondok Pesantren Universitas Islam Indonesia, 2026)
This study examines the historical background as well as the forms and mechanisms of Western colonialism in the Muslim world, emphasizing that the decline of Muslim societies should be understood as a historical and structural phenomenon rather than a consequence of Islamic theological teachings. Following the death of the Prophet Muhammad (peace be upon him), the Muslim world experienced significant political dynamics characterized by internal conflicts, the weakening of the caliphal authority, and the eventual collapse of major political powers such as the Abbasid and Ottoman empires. These conditions created structural vulnerabilities that enabled the penetration of external powers. At the same time, the stagnation of scientific and intellectual development, along with the decline of political support for scholarly traditions, further limited the capacity of Muslim societies to respond to global transformations. Within this context, European expansion into Muslim territories occurred gradually, beginning with the Reconquista in Andalusia, the Crusades, the maritime expansion of Iberian powers, and eventually the emergence of modern colonialism in the nineteenth and twentieth centuries. This research employs a qualitative method with a historical-critical approach based on library research. The findings indicate that Western colonialism was not limited to military and political domination but also operated through administrative and legal control, economic exploitation, educational and cultural restructuring, and the production of ideological and discursive representations of Islam. These processes ultimately formed a complex and long-term system of colonial hegemony that significantly shaped the political, economic, and intellectual structures of Muslim societies. [Tulisan ini mengkaji latar belakang historis serta bentuk dan mekanisme kolonialisme Barat terhadap dunia Islam dengan menekankan bahwa kemunduran masyarakat Muslim merupakan fenomena historis dan struktural, bukan akibat dari ajaran teologis Islam. Sejak wafatnya Nabi Muhammad SAW, dunia Islam menghadapi berbagai dinamika politik yang ditandai oleh konflik internal, melemahnya institusi kekhalifahan, serta runtuhnya kekuatan politik besar seperti Dinasti Abbasiyah dan Kesultanan Utsmani. Kondisi tersebut menciptakan kerentanan struktural yang membuka peluang bagi penetrasi kekuatan eksternal. Di sisi lain, stagnasi perkembangan ilmu pengetahuan dan melemahnya dukungan politik terhadap tradisi intelektual turut memperlemah kemampuan dunia Islam dalam merespons perubahan global. Dalam konteks tersebut, ekspansi Eropa ke wilayah-wilayah Muslim berlangsung secara bertahap, mulai dari Reconquista di Andalusia, Perang Salib, ekspansi maritim bangsa Iberia, hingga kolonialisme modern pada abad ke-19 dan ke-20. Penelitian ini menggunakan metode kualitatif dengan pendekatan historis-kritis berbasis studi kepustakaan. Hasil penelitian menunjukkan bahwa kolonialisme Barat tidak hanya berlangsung melalui dominasi militer dan politik, tetapi juga melalui kontrol administratif dan hukum, eksploitasi ekonomi, rekayasa pendidikan dan budaya, serta produksi wacana ideologis tentang Islam. Proses tersebut membentuk sistem hegemoni kolonial yang berdampak jangka panjang terhadap struktur politik, ekonomi, dan intelektual masyarakat Muslim.]